"Changing in favour of the team": the collective dimension in the work of beach volleyball athletes - Louise Borba (Universidade do Porto, 2017)
Thinking on the collective dimension of sports as a division of functions among athletes within a team may limit and conceal all the existing debates and dramas in such work activity. Thus, the aim of the present study is to assess how autonomous beach volleyball athletes manage their professional lives in the search for partners to form a pair who fits for "playing together", although the work organisation in the aforementioned modality is extremely competitive and requires high turnover of its members. Based on Ergology, Ergonomics and Clinic Activity, we assume that athletes are required to put their sportive competences in synergy to form a pair, or to set up a team. Besides, above all, we expected these athletes to be able to build cognitive references, as well as common values, which enable communication and cooperation within work development.